Effects of date palm pollen on fertility and development of reproductive system in female Balb/C mice - Moshfegh Fazeleh; Baharara Javad; Namvar Farideh; Zafar-Balanezhad Saeedeh; Amini Elahe; Jafarzadeh Lobat (Shahrekord University of Medical Sciences, 2016)
Introduction: The Phoenix dactylifera or date palm pollen (DPP) is widely used for male infertilityin traditional medicine. The aim of this study was to evaluate the effect of DPP on fertility and development of female reproductive system in Balb/C mice.Methods: Ten groups were assigned to 2 control and 8 experimental groups. On the control groups1 and 2 no treatment was conducted, but in the control group 2, after 10 days the mice were mated.In experimental groups 1 and 2, the animals received DPP (100 and 200 mg/kg, respectively) byoral administration for 10 days. In experimental groups 3 and 4 percentage of mating was evaluatedafter 10 days. Experimental groups 5 and 6 received DPP during gestation. Embryos were removedto evaluate ovaries histology. For experimental groups 7 and 8, DPP was administered until 21thday after birth. The offspring ovaries were removed to evaluate histological parameters. The levelsof sexual hormones were also measured.Results: Several parameters of ovaries in offspring, including mass index, diameter of ovaries,number of primary and secondary graph follicles and corpora luteal, percentage of mating, bodymass index and Crown rump (CR) of embryos, diameter of ovary, basic sexual cell number inembryos, and mass index increased in experimental groups in comparison to the controls.However, luteinizing hormone (LH) and follicle-stimulating hormone (FSH) in the experimentalgroups were not significantly different from those in control groups (P > 0.05), while estrogen andprogesterone considerably increased in experimental groups (P < 0.05).Conclusion: Results of our investigation propose that DPP can create an appropriate situationfor oogenesis and maintain efficient fertility in female mice which it may be considered as usefulnutraceuticals for potentiation of fertility in future human studies.